REVIEWS (Heythrop journal, 1971)
Book reviewed in this article: Dialectical Christianity and Christian Materialism. By R. C. Zaehner. Evolution in Religion. A Study in Sri Aurobindo and Pierre Teilhard de Chardin. By R. C. Zaehner. The Object of Morality. By G. J. Warnock. Ascent to the Absolute. By J. N. Findlay. Glaube, Gnade, Geschichte: Die Glaubenstheologie des Pierre Rousselot S. J. By Erhard Kunz. Basic Questions in Theology. By Wolfhart Pannenberg. Translated by George H. Kehm. Resurrection and the New Testament. By C. F. Evans. The Gospel according to John. Translated with an Introduction and Notes by R. E. Brown. Two volumes with continuous pagination, Clement of Alexandria's Treatment of the Problem of Evil. By W. E. G. Floyd. Lexikon der christlichen Ikonographie. Vol. II, Allgemeine Ikonographie, F-K. Edited by Engelbert Kirschbaum, S. J. The Archaeology of the New Testament. The Life of Jesus and the Beginning of the Early Church. By Jack Finegan. The Christian Priesthood. Ninth Downside Symposium. Edited by Nicholas Lash and Joseph Rhymer. Rethinking the Priesthood. Edited by F. V. Johannes. Man for Others. Reflections on Christian Priesthood. By John Jay Hughes. A Short History of the Western Liturgy. An Account and some Reflection. By Theodore Klauser. Monarchy and Community. Political Ideas in the later Conciliar Controversy, 1430–1450. By A. J. Black. Humanism in France at the end of the Middle Ages and in the Early Renaissance. Edited by A. H. T. Levi. Christendom Divided. By Hans J. Hillerbrand. Hope and Planning. By Jüurgen Moltmann.